TREM-1+ Macrophages Define a Pathogenic Cell Subset in the Intestine of Crohn's Disease Patients. (4th February 2021) - Caër, Charles; Gorreja, Frida; Forsskåhl, Sophia K; Brynjolfsson, Siggeir F; Szeponik, Louis; Magnusson, Maria K; Börjesson, Lars G; Block, Mattias; Bexe-Lindskog, Elinor; Wick, Mary Jo
Abstract: Background and Aims: Uncontrolled activation of intestinal mononuclear phagocytes [MNPs] drives chronic inflammation in inflammatory bowel disease [IBD]. Triggering receptor expressed on myeloid cells 1 [TREM-1] has been implicated in the pathogenesis of IBD. However, the role of TREM-1 + cell subsets in driving IBD pathology and the link with clinical parameters are not understood. We investigated TREM-1 expression in human intestinal MNP subsets and examined blocking TREM-1 as a potential IBD therapy. Methods: TREM-1 gene expression was analysed in intestinal mucosa, enriched epithelial and lamina propria [LP] layers, and purified cells from controls and IBD patients. TREM-1 protein on immune cells was assessed by flow cytometry and immunofluorescence microscopy. Blood monocyte activation was examined by large-scale gene expression using a TREM-1 agonist or LP conditioned media [LP-CM] from patients in the presence or absence of TREM-1 and tumour necrosis factor [TNF] antagonist antibodies. Results: TREM-1 gene expression increases in intestinal mucosa from IBD patients and correlates with disease score. TREM-1 + cells, which are mainly immature macrophages and CD11b + granulocytes, increase among LP cells from Crohn's disease patients and their frequency correlates with inflammatory molecules in LP-CM. LP-CM from Crohn's disease patients induces an inflammatory transcriptome in blood monocytes, including increased IL-6 expression, which is reduced by simultaneous blocking of TREM-1 and TNF. Conclusions: High intestinal TREM-1 expression, reflecting a high frequency of TREM-1 + immature macrophages and TREM-1 + CD11b + granulocytes, is linked to the deleterious inflammatory microenvironment in IBD patients. Therefore, blocking the TREM-1 pathway, especially simultaneously with anti-TNF therapy, has potential as a new IBD therapy.